KUALITAS PELAYANAN PENDIDIKAN BERBASIS PELAKSANAAN OTONOMI DAERAH PROVINSI JAWA TIMUR - Anggraeny Puspaningtyas (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2018)
The opening of the 1945 Constitution of the Republic of Indonesia states that the national objective of the Indonesian state is to educate the life of the nation, create public welfare, protect all of Indonesia's bloodshed, and help implement world order and lasting peace. Efforts to achieve these national goals can be done through the fulfillment of basic rights of the community, one of which is through education. Republic of Indonesia Government Regulation Number 2 of 2018th concerning Minimum Service Standards (Standart Pelayanan Mutu/SPM) that compulsory government affairs relating to basic services consist of education; health; public works and spatial planning; public housing and residential areas; peace, public order and community and social protection. Furthermore, the education SPM includes the Provincial Education SPM and the District/City Education SPM. The types of basic services in the SPM of Provincial Education consist of secondary education and special education. While the types of basic services in the district/city education SPM consist of early childhood education, basic education and equality education. The researcher was interested in knowing how the quality of regional autonomy-based education services in East Java Province.